Suitability of residues from seaweed and fish processing for composting and as fertilizer - Cabell, Joshua; Eich-Greatorex, Susanne; Ion, Violeta Alexandra; Krogstad, Tore; Matsia, Sevasti; Perikli, Maria; Salifoglou, Athanasios; Løes, Anne-Kristin (2024)
There is a need to find novel sources of fertilizers to meet the increasing food demands of a growing human population and alternatives to mined and synthetic fertilizers for the certified organic sector. Marine residues contain all (micro-)macro-nutrients that plants need. Composting is a common method for processing organic residues for use in horticulture. To that end, a small-scale composting experiment was conducted in Dewar flasks with five marine residues mixed in six combinations: dried and ground rockweed (Ascophyllum nodosum), algae fiber from chemically processed rockweed, ground fish bones and fishmeal from cod (Gadus morhua), and ground blue mussels (Mytilus edulis). Physicochemical analyses were run on the residues and their mixtures before and after composting, with the temperature monitored over 92 days. The goal was to assess whether these residues were suitable for aerobic composting, based on tem-perature profiles and changes in physiochemical parameters, and to evaluate the final composts as potential fertilizers. The combination of algae fiber and fishmeal generated the highest heat and exhibited the greatest reduction in volume. None of the finished composts, however, were sufficiently balanced for use as fertilizers alone, but they could provide valuable organic matter and nutrients in combination with other nutrient sources.